2017
DOI: 10.1051/0004-6361/201630244
|View full text |Cite
|
Sign up to set email alerts
|

Bars and boxy/peanut bulges in thin and thick discs

Abstract: We explore trends in the morphology and line-of-sight (los) velocity of stellar populations in the inner regions of disc galaxies using N-body simulations with a thin (kinematically cold) and a thick (kinematically hot) disc which form a bar and a boxy/peanut (b/p) bulge. The bar in the thin disc component is ∼50% stronger than the thick disc bar and is more elongated, with an axis ratio almost half that of the thick disc bar. The thin disc b/p bulge has a pronounced X-shape, while the thick disc b/p is weaker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 86 publications
11
88
0
Order By: Relevance
“…These results indicate that intermediate age stellar populations are concentrated on more elongated orbits closer to the bar major axis than older stellar populations. They are consistent with the findings from idealised thin (kinematically cold/young) plus thick (kinematically hot/old) disc N-body galaxy simulations in Fragkoudi et al (2017). In their figure 2, they show that the colder component forms a strong and thin bar, while the hotter component forms a weaker and rounder bar (see also Wozniak 2007;Athanassoula et al 2017;Debattista et al 2017;Fragkoudi et al 2018).…”
Section: Star Formation Historiessupporting
confidence: 87%
See 2 more Smart Citations
“…These results indicate that intermediate age stellar populations are concentrated on more elongated orbits closer to the bar major axis than older stellar populations. They are consistent with the findings from idealised thin (kinematically cold/young) plus thick (kinematically hot/old) disc N-body galaxy simulations in Fragkoudi et al (2017). In their figure 2, they show that the colder component forms a strong and thin bar, while the hotter component forms a weaker and rounder bar (see also Wozniak 2007;Athanassoula et al 2017;Debattista et al 2017;Fragkoudi et al 2018).…”
Section: Star Formation Historiessupporting
confidence: 87%
“…We see that the youngest population has an elongated bar shape, much more so than the oldest population which is rounder. This difference in the shape of the bar according to the age and kinematics of the underlying population was shown using idealised simulations in Fragkoudi et al (2017) and Athanassoula et al (2017), and was termed kinematic fractionation by Debattista et al (2017). Therefore we see that the younger populations are more clustered along the bar major axis than the oldest populations, due to kinematic fractionation, giving rise to the V-shape we see in the observations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Multiple studies, based on stellar populations and numerical simulations, have shown evidence that the Milky Way's central 'bulge' is not (primarily) the remnant of past merger events, i.e., a 'classical' bulge, but rather it was built predominantly from disc stars through the buckling and secular evolution of the Galactic bar, the latter itself originating from the disc (Shen et al 2010, Ness et al 2012Di Matteo et al 2014;Di Matteo 2016;Abbott et al 2017; see also Fragkoudi et al 2017). This result is consistent with the X/P morphology and indicates that the X/P 'bulge' and bar are aligned, since one has formed from, and is still the thick central part of, the other (see also Martinez-Valpuesta & Gerhard 2011, Romero-Gómez et al 2011and Wegg, Gerhard & Portail 2015.…”
Section: The (X/p Structure + Bar) Geometrymentioning
confidence: 99%
“…Debattista et al (2016) recently studied bar formation in galaxies that contain disc populations with differing random motions. They showed that radially cooler populations form stronger bars, the edge-on profiles of which are vertically thinner and peanut-shaped, whereas the hotter populations form a weaker bar with a vertically thicker edge-on box shape (see also Fragkoudi et al 2017).…”
Section: The Edge-on Structure Of Barsmentioning
confidence: 94%